A prognostic eight‐lncRNA expression signature in predicting recurrence of ER‐positive breast cancer receiving endocrine therapy. Issue 5 (29th October 2019) - Tang, Jianing; Cui, Qiuxia; Zhang, Dan; Kong, Deguang; Liao, Xing; Ren, Jiangbo; Gong, Yan; Wu, Gaosong
Abstract: Long noncoding RNAs (lncRNAs) have the main role in the tumorigenesis of breast cancer. In the present study, lncRNA expression profiling was collected to identify a lncRNA expression signature from the Gene Expression Omnibus database. An eight‐lncRNA signature was established to predict the survival of patients with estrogen receptor (ER)‐positive breast cancer receiving endocrine therapy. Patients were separated into a low‐risk group and a high‐risk group based on this signature. Patients in high‐risk group have worse survival compared to those in low‐risk group using Kaplan–Meier curve analysis with log‐rank test. Receiver operating characteristic analysis suggested good diagnostic efficiency of the eight‐lncRNA signature. When adjusting the clinical features, including age, grade, lymph node status, and tumor size, this signature was independently associated with the relapse‐free survival. The prognostic value of the lncRNA prognostic model was then validated in validation sets. When validated in a cohort of patients treated with neoadjuvant chemotherapy and endocrine therapy, this signature demonstrated good performance as well. Besides, we have built a nomogram that integrated the conventional clinicopathological features and the eight‐lncRNA‐based signature. To sum up, our results indicated that the eight‐lncRNA prognostic model was a reliable tool to group patients at high and low risk of disease relapse. This signature may have possible implication in prognostic evaluations of patients with ER‐positive breast cancer receiving endocrine therapy. Abstract : We established an eight‐long noncoding RNA (lncRNA) signature to predict the survival of patients with estrogen receptor‐positive breast cancer receiving endocrine therapy. We have built a nomogram that integrated the conventional clinicopathological features and the eight‐lncRNA‐based signature.